Behavioural, immunological and transcriptomic consequences of post-weaning social isolation and chronic celecoxib administration in mouse - Aodán Laighneach; Derek W. Morris; Saahithh Redddi Patlola; Marcelo Improta; Lieve Desbonnet; Gary Donohoe; John P. Kelly; Declan P. McKernan (PLoS ONE, 2025)
Early life stress (ELS) and chronic low-grade inflammation are associated with psychiatric disease risk, but their neurobiological consequences are poorly understood. Here, we aim to investigate the behavioural, immunological and molecular consequences of ELS in mice. C57Bl6 mice were subjected to post-weaning social isolation (SI - PD21−40) with or without chronic celecoxib (CEL) (PD21−61). ELS-induced behavioural changes were assessed using the open field test (OFT) and three-chambered test (3CT). The anti-inflammatory effects of celecoxib were assessed by enzyme-linked immunosorbent assay (ELISA) of IL-6, TNF-α and IL-10 cytokines released by stimulated splenocytes. Gene expression changes in the hippocampus and amygdala were assessed using RNA-sequencing. Neither SI nor CEL affected OFT time in centre or 3CT discrimination ratio. However, SI induced locomotor changes in both tests. CEL significantly reduced IL-6, TNF-α and IL-10 release from splenocytes. SI induced significant gene expression changes in both hippocampus and amygdala, while CEL only induced gene expression changes in the hippocampus. Differentially expressed genes (DEGs) induced by SI were enriched for ontologies relating to gamma-aminobutyric acid activity and insulin binding in the hippocampus and neurogenesis in the amygdala. CEL-induced DEGs in the hippocampus were enriched for neurogenesis. Cell type enrichment implicated choroid plexus and vascular leptomeningeal cells in SI DEGs and medium spiny neurons (MSNs) in CEL DEGs. CEL-induced DEGs were enriched for heritability for psychiatric disorders and cognitive ability. In conclusion, gene expression changes show convergence with human psychiatric disorders through both enrichments in common genetic heritability and enrichment of previously implicated cell populations.